2019
DOI: 10.1007/s13659-019-0204-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative-Profiling Method of Serum Steroid Hormones by Hydroxylamine-Derivatization HPLC–MS

Abstract: A sensitive and rapid high performance liquid chromatography–mass spectrometry (HPLC–MS) method was developed and validated for simultaneous quantification of ten steroid hormones, including estrogens, androgens, progesterones, and corticosteroids four classes of steroids. The following ten steroid hormones were analyzed: progesterone, 21-deoxycortisol, estrone, 4-androstenedione, testosterone, dihydro-testosterone, androstenone, dehydroepiandrosterone, corticosterone and cortisone. Stable deuterated isotopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…However, preliminary derivatization is still used for this type of analysis, using a targeted modification of steroid substructures. Such approaches, including the conversion of carbonyl groups by reaction with hydroxylamine or 2-hydrazinopyridine, were proposed for the highly sensitive determination of endosteroids by HPLC/ESI-MS and UHPLC/ESI-MS [ 101 ], respectively. We can also note a preliminary modification of carbonyl groups with the introduction of a fixed charge (Girard’s reagent), carried out to detect and determine off-target steroid metabolites by a combined method of LC with high-resolution MS (LTQ-Orbitrap) [ 102 ].…”
Section: Mass Spectrometry In Omics Life Sciencesmentioning
confidence: 99%
“…However, preliminary derivatization is still used for this type of analysis, using a targeted modification of steroid substructures. Such approaches, including the conversion of carbonyl groups by reaction with hydroxylamine or 2-hydrazinopyridine, were proposed for the highly sensitive determination of endosteroids by HPLC/ESI-MS and UHPLC/ESI-MS [ 101 ], respectively. We can also note a preliminary modification of carbonyl groups with the introduction of a fixed charge (Girard’s reagent), carried out to detect and determine off-target steroid metabolites by a combined method of LC with high-resolution MS (LTQ-Orbitrap) [ 102 ].…”
Section: Mass Spectrometry In Omics Life Sciencesmentioning
confidence: 99%
“…However, the poor hydrophobicity of NH 2 OH itself has limitation to improve the retention of metabolites. Liu et al [88] quantified ten steroid hormones by hydroxylamine derivatization using HPLC-MS and a LOQ was achieved in the range of 0.05-5 ng/mL which was increased by 3.9-202.6 times after derivatization. Because hydroxylamine reacts fast and shows no contaminations to MS, Chen et al [89] developed a fully automated in-tube SPME/LC-PCD-MS method, and demonstrated rapid and accurate quantification of urinary hexanal and heptanal by simple sample preparation and avoiding LC separation of E-/Zisomers of oximes (Figure 4).…”
Section: Hydroxylaminesmentioning
confidence: 99%
“…In addition, it was possible to inject the reaction mixture into the chromatograph without additional purification steps after obtaining the derivatives. Hydroxylamine was previously used to determine steroid hormones in human biological fluids with high sensitivity [3,23,24]. Scheme 1 shows the derivatization reaction using hydroxylamine as a derivatizing agent.…”
Section: Articlesmentioning
confidence: 99%